Determinan Kepemilikan Jaminan Kesehatan di Provinsi Kalimantan Timur: Analisis Data SKI 2023 - Eka Putri Rahayu; Rea Ariyanti; Rahayu, Agustin Putri (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
National Health Insurance (JKN) is the government's commitment to protecting public health. Health insurance is a system designed to ensure access to health services for all levels of society without exception. In Indonesia, health insurance is implemented through the National Health Insurance (JKN) program managed by the Social Security Administering Agency (BPJS) Health. This program aims to provide comprehensive health protection for all citizens through a mutual cooperation system. The purpose of this study was to analyze the determinants of ownership of National Health Insurance (JKN) in East Kalimantan Province. Indonesian Health (SKI) in 2023 with a cross-sectional research design. Respondents registered for health insurance ownership in East Kalimantan province amounted to 12,418 respondents. Data were analyzed using univariate and bivariate methods. Univariate data analysis was carried out with the results in the form of a frequency table. Bivariate data analysis used the Chi Square test. Determinants of health insurance ownership were significantly influenced by marital status, education level and employment status with each variable having a p-value <0.05. The results of this study can be the basis for the development of health policies, especially national health insurance.